2019
DOI: 10.1002/mp.13922
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a plastic scintillating plate‐based treatment beam fluence monitoring system for use in pencil beam scanning proton therapy

Abstract: Purpose The purpose of this study was to describe a plastic scintillating plate‐based gantry‐attachable dosimetry system for pencil beam scanning proton therapy to monitor entrance proton beam fluence, and to evaluate the dosimetric characteristics of this system and its feasibility for clinical use. Methods The dosimetry system, consisting of a plastic scintillating plate and a CMOS camera, was attached to a dedicated scanning nozzle and scintillation during proton beam irradiation was recorded. Dose distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…In proton therapy, the entrance dose was measured using an optical fiber and a plastic scintillator to monitor treatment beam, and perturbations induced by these devices were evaluated by measuring differences in spot sizes and ranges in their presence and absence. 47,48 Similarly, when the SC-IVD (100 mg of scintillating powder) was placed on the phantom surface, it was found that the dose at R90, usually used as the prescription depth, was reduced by 2.2% for the 6 MeV electron beam energy compared to the case without the SC-IVD. The percent dose reduction was lower at higher electron beam energy and higher at R50, which was sensitive to the measurement depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In proton therapy, the entrance dose was measured using an optical fiber and a plastic scintillator to monitor treatment beam, and perturbations induced by these devices were evaluated by measuring differences in spot sizes and ranges in their presence and absence. 47,48 Similarly, when the SC-IVD (100 mg of scintillating powder) was placed on the phantom surface, it was found that the dose at R90, usually used as the prescription depth, was reduced by 2.2% for the 6 MeV electron beam energy compared to the case without the SC-IVD. The percent dose reduction was lower at higher electron beam energy and higher at R50, which was sensitive to the measurement depth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have evaluated the transmission factor for Dolphin, a commercial transmission detector, to determine the feasibility of using it online during treatment. In proton therapy, the entrance dose was measured using an optical fiber and a plastic scintillator to monitor treatment beam, and perturbations induced by these devices were evaluated by measuring differences in spot sizes and ranges in their presence and absence 47,48 . Similarly, when the SC‐IVD (100 mg of scintillating powder) was placed on the phantom surface, it was found that the dose at R90, usually used as the prescription depth, was reduced by 2.2% for the 6 MeV electron beam energy compared to the case without the SC‐IVD.…”
Section: Discussionmentioning
confidence: 99%
“…Scintillation imaging has been routinely utilized for proton beams with the use of commercial scintillator‐based systems for quality assurance 4,5 or in‐house developed systems 6–11 . High temporal resolution can be obtained by using a fast camera.…”
Section: Introductionmentioning
confidence: 99%
“…Scintillation imaging has been routinely utilized for proton beams with the use of commercial scintillatorbased systems for quality assurance 4,5 or in-house developed systems. [6][7][8][9][10][11] High temporal resolution can be obtained by using a fast camera. So far, this has been employed for PBS proton irradiations at conventional dose rates from a cyclotron 12,13 and a synchrocyclotron 14,15 as well as for electron UHDR irradiations, 16 exhibiting great potential for dosimetry for FLASH radiotherapy.…”
Section: Introductionmentioning
confidence: 99%